Digital Media Image of Business University Professor - M. A. Lukashenko; N. V. Gromova; A. A. Ozhgikhina (Высшее образование в России)
Digitalization of business and society inevitably affects almost all spheres, and education is not an exception. New high-tech tools and solutions are rapidly coming into this industry, without which further development and implementation of the educational process is no longer possible. Today target audience of any educational organizations is informationally advanced and prefers to source useful information from social networks, often making business decisions based on it. Such conditions put forward new requirements for educational organizations to increase their activity in social networks and, above all, to form a digital image. Professors are the face of any educational organization. Inasmuch as they are the subjects who directly interact with students, their personal digital image plays an important role in shaping corporate image of the university. Relevance of this article is in the research of the digital image process formation by professors of business universities, which are the flagships and market-oriented subjects of local higher education.The article aims to identify the current state of forming the digital image of teachers of entrepreneurial universities in social networks. To achieve the goal, the article discusses the features of an entrepreneurial university and the characteristics of its corporate image, shows the need to form a teacher’s digital image and identifies strategies for such formation in social networks. The study of the activity of Russian entrepreneurial universities’ teachers in social networks was carried out and the comparison of the results with the similar activity of foreign universities’ teachers was made.